Kualitas Produk, Harga, Promosi Penjualan dan Iklan Serta Pengaruhnya terhadap Keputusan Pembelian pada Toko Online Bukalapak - Rahmad Efendy; Roma Pasaribu; Ratna Ashary; Putri Nabila; Raymond Fransiscus (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the influence of Product Quality, Price, Sales Promotion, and Advertising on consumer purchasing decisions on the Bukalapak online store platform. This study used a quantitative approach with descriptive methods, aiming to illustrate the relationships between variables based on empirical data. Primary data were obtained by distributing questionnaires to 120 respondents who were active Bukalapak users in the West Medan District. The data analysis technique used was multiple linear regression with the aid of SPSS software to determine the effect of each independent variable on the dependent variable. The analysis results indicate that, partially, the variables Product Quality, Sales Promotion, and Advertising have a positive and significant influence on purchasing decisions. This means that the higher the product quality, the more effective the promotion, and the more attractive the advertisement, the greater the likelihood of consumers making a purchase. Conversely, the variable Price showed a negative and significant influence, indicating that inappropriate pricing can reduce purchase intention. Simultaneously, all four variables have a significant influence on purchasing decisions. The Adjusted R Square value of 70.4% indicates that this research model is able to explain 70.4% of the variation in purchasing decisions, while the dependent variable is influenced by factors outside the model. This study recommends that Bukalapak continue to improve product quality, develop competitive pricing strategies, strengthen promotions, and create creative advertising. Further research is recommended to consider additional variables such as product reviews, brand image, and service quality to enrich the analysis.